Transperitoneal Laparoscopic Adrenalectomy: Assessment of the Surgical Learning Curve. (8th October 2013) - Meier, Lukas; Zulewski, Henryk; Oertli, Daniel
Abstract : Background. We report a single surgeon's experience of 52 transperitoneal laparoscopic adrenalectomies (LAs) performed between 2001 and 2010. In addition, we compared this series with our first published series of LAs performed between 1994 and 2001. Methods. Our series includes 24 left, 20 right, and 4 bilateral LAs performed in 48 patients. To estimate the learning curve, we chronologically divided the sample of unilateral LAs into two groups of 22 patients and compared the operating time, estimated blood loss, maximum diameter of the lesion, complications, and length of hospital stay. Results. Mean operating time was significantly lower (94 versus 78 min, P < 0.05 ) and mean intraoperative blood loss was significantly lower (156 versus 60 mL, P < 0.05 ) after more experience had been gained. Additionally, a trend towards removing larger lesions was observed. There was no significant difference in terms of hospital stay. Conclusions. Observing a single surgeon's experience of nine years in laparoscopic adrenalectomy, this study indicates that it takes approximately 20–25 procedures to flatten the learning curve. Thus, for single centers with a volume of approximately five LAs performed per year, we suggest a selection of a few experienced surgeons to perform LAs in order to improve outcomes.